Z zagadnień struktury rządu NRF: [On the structure of the Federal Republic of Germany government] (Studia Prawnicze / The Legal Studies, 1971)
Autor artykułu przybliża czytelnikom zagadnienia dotyczące władzy wykonawczej w Niemieckiej Republice Federalnej. Wskazuje na koncentrację coraz większej władzy w rękach egzekutywy. Autor wnikliwie przedstawia regulacje prawne dotyczące stanowiska kanclerza w systemie prawnym NRF, w której opisuje m. in. zakres kompetencji czy procedurę powoływania kanclerza. Opisuje ponadto status prawny pozostałych członków rządu, ministrów i organu kolegialnego złożonego zarówno z kanclerza jak i z ministrów. Analiza oparta jest na przepisach zawartych w ustawie zasadniczej NRF oraz w regulaminie wewnętrznym rządu. The author of this article introduces readers to issues concerning the executive in the Federal Republic of Germany. It points to the concentration of increasing power in the hands of the executive. The author provides an in-depth overview of the legal regulation of the position of Chancellor in the legal system of the Federal Republic of Germany, in which he describes, among other things, the scope of powers or the procedure for the appointment of the Chancellor. He further describes the legal status of the other members of the government, the ministers and the collegiate body comprising both the Chancellor and the ministers. The analysis is based on the provisions contained in the constitution of the Federal Republic of Germany and the government's rules.